Micromobility in Thessaloniki, Greece, and Madrid, Spain: a comparative study. Issue 1 (November 2021) - Alevras, Dimitrios; Zinas, Dimitrios; Palantzas, Georgios; Genitsaris, Evangelos; Nalmpantis, Dimitrios
Abstract: The purpose of this paper is to present the benefits, risks, problems, and ways to improve the service of Lime S electric scooters (e-scooters) in the cities of Thessaloniki, Greece, and Madrid, Spain. The aim of the paper is to present the service's transportation benefits and to investigate the improvement rate it has offered in urban transport in these major cities. The methodology used is a literature review together with a questionnaire survey, which was distributed via the Internet to users of the service in the two cities. The content of the questions mainly focuses on the reasons why they use e-scooters, how happy they are with the service they are provided, and the ways in which it could be improved. Finally, we conclude that the more the Lime S service operates, the more the acceptance of the citizens of both cities it gains. Users respect the ease and speed of the travel they are provided, as well as the ecological character of the company. We can also see a demand for improving the service, both in the area of security, e.g., making helmets mandatory (≈57%), and in the legislative framework regulating its operation, e.g., compulsory ride on bicycle lanes (≈36%) and imposing age restrictions (≈29%). It is certain that in addition to the responsibility of the company for the users, the states and the users' responsibilities are also important in order to ensure better and safer travels.